2015
DOI: 10.1007/s00428-015-1747-2
|View full text |Cite
|
Sign up to set email alerts
|

HER3 protein expression in relation to HER2 positivity in patients with primary colorectal cancer: clinical relevance and prognostic value

Abstract: The clinical and prognostic significance of HER3 expression and its relation to HER2 status in primary colorectal cancer (pCRC) were investigated. We retrospectively analysed 365 consecutive cases of pCRC that had been previously evaluated for HER2 status and included their 143 matched lymph node metastases. Immunohistochemistry (IHC) was performed to assess HER3 expression using tissue array methods. Of 364 eligible patients, HER3 overexpression was detected in 251 cases (69 %) (IHC 2+, n = 186 and IHC 3+, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 40 publications
3
20
1
Order By: Relevance
“…Unlike a previous investigation, we could not associate HER3 expression with NRG1 expression [19]. In our investigation, regular simultaneous expression of HER2/neu and HER3 was also not detected, although coexpression of HER2/neu and HER3 has been described in cohort of 364 surgically resected CRC patients [28]. The latter discrepancy might be caused in part by the different clinical backgrounds of patients as well as by the different diagnostic methods used.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Unlike a previous investigation, we could not associate HER3 expression with NRG1 expression [19]. In our investigation, regular simultaneous expression of HER2/neu and HER3 was also not detected, although coexpression of HER2/neu and HER3 has been described in cohort of 364 surgically resected CRC patients [28]. The latter discrepancy might be caused in part by the different clinical backgrounds of patients as well as by the different diagnostic methods used.…”
Section: Discussioncontrasting
confidence: 97%
“…The sample size of patients with HER2/neu overexpression in our cohort does not allow for conclusions on the prognostic impact. It is noteworthy that HER3 overexpression was not associated with an unfavourable outcome in FIRE-1, although conflicting data may exist [16][17][18]24,28]. However, the small number of patients enrolled in some trials limits conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…Our data also demonstrated that HER2 expression is more common in big primary tumor size than in small size. This finding is similar to the findings of previous studies (19). In addition, big primary tumor had significantly higher 18 F-FDG uptake than did small primary tumor, partly explaining why patients with HER2 expression had a high SUVmax.…”
Section: Discussionsupporting
confidence: 91%
“…for breast and colorectal cancer[ 13 , 58 , 59 ]. Moreover, HER3 may function as a signalling hub for the HER family, that leads to compensatory pathways when other HER receptors are blocked[ 60 ], thus promoting resistance to multiple therapeutic agents[ 12 , 15 , 24 ]. For TKIs, this appears to happen by a compensatory upregulation of membranous HER3, possibly due to MET-amplification[ 43 ], via a shift in the HER3 phosphorylation-dephosphorylation equilibrium, making the effect of the drug transient[ 11 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the results from this study, the majority of reports on the prognostic impact of EGFR expression in gastric and esophageal adenocarcinoma have demonstrated correlations with shorter OS[ 20 , 21 , 29 , 33 ], although one study found an independent correlation to a longer OS[ 63 ]. HER3 expression has also been correlated with shorter OS in gastric as well as other cancer forms[ 17 , 19 , 26 ], but also with longer, or trends towards longer, OS in colorectal and breast cancer[ 60 , 64 , 65 ]. Other studies could not demonstrate any prognostic impact for EGFR[ 26 , 27 , 32 ] or HER3 [ 27 ] in upper gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%